Financial Autonomy of Local Self-Governments in the Republic of Serbia and the Republic of Poland – Comparative Analysis - Kaźmierczak, Mateusz; Živanović, Filip (Central European Academy Law Review, 2023)
This contribution deals with the concept of financial autonomy of the local self-governments in the Republic of Poland and the Republic of Serbia. The main aim of this contribution is to confirm or disprove the hypothesis that in the abovementioned countries current legal system is in line with the financial autonomy requirements stipulated by the European Charter of Local Self-Governments. The research is conducted by applying basic methods of legal science, especially the method of scientific analysis. First, it provides a brief overview of the Charter’s role, constitutional background of Serbia and Poland. Second, it present the regulation on local taxation in the abovementioned countries and its place within the local budgets. Third, it confronts the results of previous analysis with the requirements of the Charter. The authors argue, that in both countries, the requirements of the Charter are only partially met.